PARENTING STYLES AND SOCIAL-EMOTIONAL READINESS OF FIRST-GRADE STUDENTS: A PHENOMENOLOGICAL STUDY - Hidayah, Hidayah; Sulistyaningsih, Wiwik (Erudio Journal of Educational Innovation, 2026)
This phenomenological research investigated the relationship between parenting styles and social-emotional readiness among first-grade students at SDN Lagoa 01 Jakarta. Preliminary questionnaires administered to thirty-two parents identified parenting style distributions (84.4% authoritative, 12.5% authoritarian, 3.1% permissive), with purposive sampling selecting eleven parents and four teachers for in-depth semi-structured interviews complemented by classroom observations. Thematic analysis revealed that authoritative parenting—characterized by warmth, emotional responsiveness, clear rules, and consistent enforcement—was most strongly associated with children's social-emotional school readiness across five indicators: emotional regulation, social interaction, rule-following, independence, and routine adaptation. Children from authoritative homes demonstrated superior emotional regulation and social competence compared to those from permissive (showing impulsivity, rule resistance, peer conflicts) or authoritarian (showing anxiety, withdrawal, fear-based compliance) environments. Parental emotional response patterns emerged as critical mechanisms, with emotion coaching fostering internalized competence while dismissive or punitive responses undermined regulation development. Teacher interventions including consistent routines, emotion coaching, cooperative learning, and parent communication effectively supported adaptation when aligned with home practices. Despite authoritative parenting predominance, 56.2% of students were categorized as "not yet ready," suggesting readiness complexity beyond parenting alone. Findings confirm social-emotional readiness results from synergistic family-school collaboration, providing evidence-based guidance for parent education programs, teacher professional development, and family-school partnership initiatives supporting children's developmental success during critical educational transitions.